The effect of fetus stimulation techniques on newborn behavior - Mahboubeh Valiani; Samira HadiAlijanvand (Iranian Journal of Nursing and Midwifery Research, 2021)
Background: Many factors affect fetal behavior, which can also affect the baby's capacity and change interaction with the caregiver. The aim of this study was to investigate the effect of performing fetal sensory systems stimulation techniques by mother during pregnancy on the neonate's habituation behavior. Materials and Methods: This semi-experimental study was conducted in 2019 in Isfahan, Iran. Mothers who referred to public comprehensive health centers in the 27th week of gestation and met the inclusion criteria were selected by convenience sampling method and randomly assigned to two groups of intervention and control. Fetal learning programs were held twice a day from the 27th week to the end of the pregnancy. The habituation domain of the neonate's behavior was assessed by the Brazelton's Neonatal Behavioral Assessment Scale (BNBAS) 3–5 days after the delivery. The mean score of habituation domain of BNBAS among 72 subjects in the intervention and control groups was compared by the Mann–Whitney test. Results: The habituation domain of all 72 newborns born approximately at the gestational age of 38 weeks was assessed. The Mann–Whitney test results indicated that the two groups were significantly different in terms of the total mean score of habituation domain 3–5 days after birth (z = –4.37, p < 0.001) and the score of the intervention group was higher than that of the control group. Conclusions: Generally, it can be concluded that the fetal stimulation techniques can positively affect the neonate's behaviors including the domain of habituation.